Cyber Threats to Press Freedom Resulting from Media Account Hijacking - Arribathi, Abdul Hamid; Ardien, Annisa; Kamal, Abdullah Arif (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
The development of digital journalism has expanded the reach of information distribution, while simultaneously increasing the vulnerability of media organizations and journalists to cyber threats that may undermine press freedom. The hacking case involving Narasi.tv demonstrates that media account hijacking is not merely an individual digital crime, but a form of systemic violence and intimidation that affects journalistic integrity and public trust. This study aims to analyze the impact of media account hijacking on press freedom and to develop an applicable technical mitigation framework for digital media organizations. The research adopts a qualitative approach using a case study of the Narasi.tv hacking incident, supported by document analysis, reports from journalist organizations, and a review of the literature on cybersecurity and digital journalism. The findings indicate that collective cyberattacks generate significant psychological and operational impacts and function as a mechanism to suppress critical journalism. This study proposes a layered mitigation framework consisting of preventive technical mitigation, newsroom operational mitigation, and public communication mitigation. Theoretically, this research extends the study of cyber threats from an individual level vulnerability toward an institutional and systemic framework. From a managerial perspective, the findings emphasize that cybersecurity must be positioned as a strategic agenda in digital media transformation. This study is also aligned with the Sustainable Development Goals, particularly SDG 16, SDG 9, and SDG 4, in supporting the development of a secure, sustainable, and trustworthy digital media ecosystem.